The pursuit of sustainability : creating business value through strategic leadership, holistic perspectives, and exceptional performance - Rainey, David L. (Emerald Publishing Limited : Information Age Publishing Inc., 2015)
The Pursuit of Sustainability: Creating Business Value through Strategic Leadership, Holistic Perspectives, and Exceptional Performance focuses on the hierarchical levels of sustainability, strategic leadership, holistic perspectives, strategic and financial performance. It also focuses on management constructs for developing and implementing cutting-edge solutions to the exciting opportunities and daunting challenges facing strategic leaders. It discusses the requisite strategic thinking, methods, techniques, and practices for examining, understanding, and managing in today's complex and turbulent business world. Sustainability and sustainable development are critical for creating positive outcomes and achieving success given the dynamics of the global economy and the ongoing shifts in customer expectations, emerging markets, and the intensity of competition.The aim of the book is to articulate concepts, constructs, and methodologies pertaining to how global corporations and small and medium size enterprises can develop and deploy enhanced solutions and more integrated systems that facilitate leading change in a more interconnected and dynamic business world. The basic perspective is that insightful strategic leaders and astute professionals and their companies can enhance performance, create extraordinary value, and sustain success through sophisticated leadership, cutting-edge management constructs, and state-of-the-art systems that reach across space and time. This includes establishing metrics on how companies can measure their progress in relation to global opportunities and challenges and the needs and expectations of people and society.The book is intended to provide strategic leaders, professionals, and practitioners with the insights, guidance, and methods for developing and implementing sustainable solutions and holistic management systems without prescribing a generalized model that supposedly would fit every situation. The strategic logic is really the opposite of the prevailing mindset of the last century in which generic concepts were developed by leading theorists (academics and business leaders) who believed that they could articulate "one-fits-all" business methods and models. In today's more complicated business world, businesses and their strategic leaders and senior professionals have to develop unique management constructs and business models for achieving the desired outcomes and sustaining success. The book describes and articulates how strategic leaders and professionals can take advantage of opportunities and challenges by addressing sustainability, sustainable development, and the pursuit of sustainability and how they can develop and deploy exciting solutions and effective systems in the quest for excellence. Excellence provides the mantra for positive change and sustainable success.The book consists of two parts. Part I examines the hierarchy of sustainability, external context, and sustainable solutions. It includes defining and examining overarching concepts and constructs pertaining to sustainability and sustainable development, highlighting the importance of the pursuit of sustainability, examining the social world and the natural environment, and discussing holistic perspectives and management constructs used to achieve sustainable success. Part II explores sustainable strategic leadership, creating business value, and management constructs pertaining to performance, vulnerabilities and sustainable success. Most importantly, Part II presents a strategic sustainability performance model that allows strategic leaders and professionals to discern where they fit in the hierarchy of sustainability.